Experimental Investigation on Effect of Inclination Angle of a Flat Plate Solar Air Collector. Issue 1 (December 2021) - Ong, K.S.; Gobi, K.; Lim, C. H.; Tan, J.C.; Naghavi, S.; Baljit, S.; Wong, S.Y.
Abstract: This study investigates the effect of inclination angle of a flat plate solar air collector in Kampar, Malaysia. Flat plate solar air collectors have been investigated since the early 1950s for air heating and crop drying. Their performances under natural convection air cooling are very similar to a photovoltaic (PV) panels for power production. A PV panel becomes hot when operating under hot weather which will affect the efficiency and lifespan. The panel could be cooled down by providing an air duct underneath which allowing natural convection air circulating inside the duct. The degree of cooling would depend upon the angle of inclination of the panel. This paper presents some experimental results on the effect of inclination angle on the performance of a flat plate solar air collector under natural convection air cooling.